Pengaruh Promosi dan Kualitas Pelayanan terhadap Kepuasan Pengunjung Event MTQ Ke-56 di Kota Medan pada PT JA Production Indonesia - Mutiara Iryanda; Jamardua Haro (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Religious events are a combination of dogma and information, rituals and appearances, piety and politics, and become habits of religious value which are framed as public spectacles. One of the religious events is the MTQ event. MTQ (Musabaqah Tilawatil Qur'an) is a competition for reading the Qur'an with mujawwad readings, namely reciting the Al-Qur'an following the legal rules of tajwid, the art of song and sound, and reading with adab recitations. In organizing an event, the important thing that must be considered by the organizers is promotion in order to notify, invite, and remind people about the event being held. The excellence of an event is not only determined by the promotion and also the type of event, but also must be supported by the quality of service. Service quality plays a very important role because it is assessed based on visitor satisfaction. If the service quality is good, the visitors who come will be happy, satisfied, and will revisit the next MTQ event. The purpose of this study was to determine whether there is an influence of promotion and service quality on visitor satisfaction.This study uses associative quantitative research with a sample of 100 respondents. The analytical method in this study is multiple linear regression with partial hypothesis testing (t test) and simultaneous testing (f test). From the test results of this study it was found that partially the promotion variable had an insignificant effect on visitor satisfaction while the service quality variable had a significant effect on visitor satisfaction. Simultaneously promotion and service quality variables have a significant influence on visitor satisfaction.